Does the tourism and travel industry really matter to economic growth and environmental degradation in the US: A sustainable policy development approach - Khan, Asif; Bibi, Sughra; Li, Hanliang; Fubing, Xue; Jiang, Shaoping; Hussain, Saddam (Frontiers in Environmental Science, 2023)
The tourism and travel industry (TTI) has become a vital developmental tool for boosting economic growth globally; however, this economic thriving is adversely connected to the environment. This study examines the impacts of eight TTI subsectors on economic growth and environmental pollution in the United States of America by contextualizing energy consumption and globalization. We applied the ARDL bounds test and Granger causality approach on time-series data (2005 1st quarter – 2019 4th quarter). Granger causality uncovers TLGH, GLTH, and feedback hypotheses between TTsubindustries. The subindustries supporting TLGH’s propose that long-run investment in these sectors could enhance economic growth. In addition, industries supporting GLTH indicate that a strong economy would be beneficial for these industries. Maximum subindustries indicate a significant positive association with energy consumption. The long-run dynamics show that TT subindustries have different influences on greenhouse gases (CO2, CH4, N2O) and air pollutants (CO, NH3, NOx, SO2, VOC, and PM2.5). Long-run dynamics show that food and drinking places emit more GHG than other entertainment and hospitality subsectors. Amusement, gambling, and entertainment contribute more to air pollutants among the entertainment and hospitality subsectors. Road and railway transportation contribute more to GHG emissions than other travel sectors in long-run. Air transportation in the travel subsector is responsible for high air pollutants. Granger casualties’ results reveal that art, gambling and recreation in entertainment and hospitality industries, and ground transportation contribute the most to environmental pollution. Globalization has varying effects on economic growth, energy consumption, and environmental pollution indicators. We have provided sustainable policy implications for reducing GHG emissions and air pollutants.